Answer:
no u
Step-by-step explanation:
Answer:
B. f(x) = -x + 11
Step-by-step explanation:
First if you rearrange the equation you get f(x) = -x + 11, like this:
x + y = 11
Minus x from both sides
y = -x + 11
F(x) and y are interchangeable so we just put f(x) in
f(x) = -x + 11
Each of the graphs are attached and we see that they are the same!
<em>Hope this helps!!</em>
<em>- Kay</em>
The equation has no solution
Answer:
x = 2
x = -21
Step-by-step explanation:
Answer:
g(x) = x^2 -6x +9
Step-by-step explanation:
A function f(x) translated right h units and up k units will become ...
g(x) = f(x -h) +k
You want the function f(x) = x^2 to be translated right h=3 units, so it will become ...
g(x) = f(x -3) = (x -3)^2
g(x) = x^2 -6x +9